Well-crystallized MIL-68(Al) prepared in isopropanol as an efficient adsorbent of furfural for wastewater abatement - Yongshiling Hu; Qi Yang; Yongsheng Liu; Yejun Guan; Jie Yang (Next Materials, 2025)
MIL-68(Al)s with different crystallinities, morphologies, and porous structures were prepared in isopropanol (IPA) and N, N’-dimethylformamide (DMF). MIL-68(Al)-IPA synthesized in IPA exhibited higher crystallinity and specific surface area than MIL-68(Al)-DMF prepared in DMF. MIL-68(Al)-IPA displayed a uniform hexagonal rod-shaped structure, whereas MIL-68 (Al)-DMF formed an irregular rod-like structure. The XRD patterns indicated a less crystallized structure in MIL-68(Al)-DMF due to the Al-OH defect sites. The furfural (FUR) adsorption capacities of the two materials depended on their specific surface areas, defect sites, and furfural concentrations. MIL-68(Al)-DMF displayed faster adsorption and a higher furfural adsorption capacity than MIL-68(Al)-IPA at furfural concentration below 6.8 g L−1, which could be explained by the presence of Al-OH sites that may enhance the interaction between the structure of MIL-68(Al)-DMF and furfural molecules. For aqueous solutions with high furfural concentrations, the furfural adsorption capacity of MIL-68(Al)-IPA surpassed that of MIL-68(Al)-DMF and gave a furfural adsorption capacity of 644.4 mg g−1 at a furfural concentration of 20.2 g L−1. The higher adsorption capacity of MIL-68 (Al)-IPA for furfural at higher furfural concentrations can be attributed to the higher specific surface area of MIL-68(Al)-IPA. MIL-68(Al)-IPA shows promising applications in wastewater abatement attributed to its low cost and environmental friendliness.